Shariah Audit Practices in Malaysia: Moving Forward - Fatihu Shehu Isa; Noraini Mohd Ariffin; Nor Hafizah Zainal Abidin (Journal of Islamic Finance, 2020)
The Shariah audit being a monitoring tool for ensuring Shariah compliance proved to be an important component in the operations of Islamic financial institutions (IFIs). In the case of Malaysia, Bank Negara Malaysia has issued a Shariah Governance Framework in 2010 which categorically made Shariah audit function as one of the required functions in IFIs in addition to Shariah Review, Shariah Research and Shariah Risk Management. In line with this, this study aimed at exploring the extent of practitioners’ awareness and perceptions of Shariah audit, the possible challenges associated with it as well as its future implications. The study used 83 practitioners drawn from various IFIs external audit firms that are involved in Shariah audit services through purposive sampling procedure. Questionnaire instrument was employed in generating the data. The findings of the study showed that practitioners’ awareness is satisfactory, as majority of them got to know about Shariah audit through an educational programme, which gave them the opportunity to express what ought to be the desirable practice of Shariah audit. Similarly, the findings revealed that the lack of the independent Shariah audit report, the standalone Shariah audit framework and the inadequate competent Shariah auditors are among the main concerns in the practice. Moreover, the findings also showed that Shariah audit will have a high potential to take up as a marketable career in the near future. Finally, the findings suggest that the integration of Shariah audit in accounting courses in institutions of higher learning; comprehensive Shariah audit framework and standards; new regulatory/professional body with a mandate of supervising IFIs as well as a professional certification in Shariah audit should be made available. It is hoped that the study will contribute towards the development of desired Shariah audit practices in Malaysia.